Fast processing of highly crosslinked, low-viscosity vitrimers. Issue 1 (29th August 2019) - Taplan, Christian; Guerre, Marc; Winne, Johan M.; Du Prez, Filip E.
Abstract : This study describes a rational approach to go beyond the current processability limits of vitrimer materials, with a demonstration of low-viscosity fast processing of highly crosslinked permanent networks. Abstract : Here we describe a rational approach to go beyond the current processability limits of vitrimer materials, with a demonstration of low-viscosity fast processing of highly crosslinked permanent networks. Vitrimers are a recently introduced class of polymer networks with a unique glass-like viscoelastic behavior, in which bond exchange reactions govern the macroscopic material flow. The restricted chain mobility, only enabled by chemical exchanges, typically limits the use of continuous processing techniques, such as extrusion or injection moulding. Herein, we outline a straightforward materials design approach, taking into account both the effect of minor additives on the chemistry of bond rearrangement as well as the macromolecular architecture of the vitrimeric network. These combined effects are demonstrated to work in an additive fashion, culminating in stress relaxation times below 1 s at 150 °C. The observed rapid bond exchanges in permanent networks result in an unprecedented control of the polymer material behavior, where the material flow is still dominated by chemical exchanges, but only marginally limited by the chemical exchange rate, overcoming the challenges encountered so far in continuous processing of highly crosslinked vitrimeric systems.